Vibro-acoustic optimisation of Wood Plastic Composite systems. (20th June 2018) - Santoni, Andrea; Bonfiglio, Paolo; Mollica, Francesco; Fausti, Patrizio; Pompoli, Francesco; Mazzanti, Valentina
Graphical abstract: Highlights: A numerical approach to characterise WPC sandwich structures is proposed. An optimisation method to improve the WPC plates' acoustic performance is provided. Orthotropic WPC plates are modelled by using frequency-depended elastic properties. An elliptic interpolation is used to approximate the orthotropic bending stiffness. An empirical equation to evaluate the bending stiffness frequency-decay is derived. Abstract: "Wood Plastic Composite" or WPC is becoming increasingly popular in outdoor applications because of the advantage of a better durability in wet environments compared to natural wood. The possibility of using WPC as a sound barrier, or as façade cladding, is investigated in this paper. The sound transmission loss (TL) of an orthotropic WPC panel, obtained by coupling together several boards, is computed by means of the transfer matrix method. The plate is modelled as a thin orthotropic layer, described by frequency dependent elastic properties. A numerical procedure, based on a finite element simulation, is proposed in order to determine the stiffness properties along the principle direction of the panel. The reliability of this approach is verified by comparing the numerical results with the experimental stiffness measured on a WPC beam. The orthotropic behaviour is approximated by an elliptic interpolation of the flexural stiffness along the two principle directions, based on a simplified assumption which considers the in-plane shear modulus proportional to the orthotropic elastic moduli. The model based within the transfer matrix method framework is validated with the experimental transmission loss measured on a WPC panel in a reverberant room. Finally, the possibility of increasing the acoustic performance of WPC structures by optimising their cross-section is investigated.